(untitled) (Società e diritti, 2023)
This essay aims to examine the issue of urban forestry because of the growing attention placed on the public agenda, especially internationally, which moves from the acquired awareness of the multifunctionality of urban forests. The presence of forests in urban centers is an element of compensation for states of pollution particularly severe in metropolitan areas, meantime it contributes to the physiognomy of urban landscapes and provides additional utility on the economic, social and cultural levels. At the national level, the promotion of urban forestry initiatives is provided by the PNRR, however, the legislative frame is poor and, first of all, is uncertain the legal definition of the term "urban forest" itself. Nevertheless, several territorial initiatives should be highlighted as virtuous expressions of subsidiarity.